A Critical Review on Selected External Physical Cues and Modulation of Cell Behavior: Magnetic Nanoparticles, Non-thermal Plasma and Lasers - Smolková, Barbora; Uzhytchak, Mariia; Lynnyk, Anna; Kubinová, Šárka; Dejneka, Alexandr; Lunov, Oleg (Journal of functional biomaterials, 2018)
Physics-based biomedical approaches have proved their importance for the advancement of medical sciences and especially in medical diagnostics and treatments. Thus, the expectations regarding development of novel promising physics-based technologies and tools are very high. This review describes the latest research advances in biomedical applications of external physical cues. We overview three distinct topics: using high-gradient magnetic fields in nanoparticle-mediated cell responses; non-thermal plasma as a novel bactericidal agent; highlights in understanding of cellular mechanisms of laser irradiation. Furthermore, we summarize the progress, challenges and opportunities in those directions. We also discuss some of the fundamental physical principles involved in the application of each cue. Considerable technological success has been achieved in those fields. However, for the successful clinical translation we have to understand the limitations of technologies. Importantly, we identify the misconceptions pervasive in the discussed fields.
Keywords: non-thermal plasma; cell signaling; lasers; cytotoxicity; magnetic nanoparticles